A Discussion of Autonomy in the Relationship Between the Law Society of Upper Canada and the University-Based Law Schools - Shanahan, Theresa (Canadian Journal of Higher Education, 2000)
This paper explores the relationship between the university-based common law schools and the Law Society of Upper Canada in legal education in Ontario today. A central objective of this paper is to distinguish between institutional autonomy and professional autonomy and to identify the competing interests and obligations of these two organizations involved in educating lawyers. In attempting to understand the differences between the autonomous bodies that govern legal education, a cross-disciplinary approach is taken to these issues combining a sociological framework on the professions with a legal perspective. The nature of professional identity and socialization, and the premise upon which professional responsibility and expertise are based is considered within the evolution of legal education in Ontario. This paper argues that the changes in organizational autonomy within the Law Society of Upper Canada and the law schools have shaped the relationship between these two bodies and increased the law school's control over legal education. In so doing this shift has powerfully influenced the future of legal education in Ontario.